Constitutive description of primary and steady-state creep deformation behaviour of tempered martensitic 9Cr–1Mo steel. Issue 21 (22nd July 2016) - Christopher, J.; Choudhary, B. K.
Abstract: The model based on the coupled sine hyperbolic creep rate relation with the evolution of internal stress as a function of strain provides better understanding of primary and secondary creep behaviour of tempered martensitic 9Cr–1Mo steel. The predicted evolution of internal stress as an increase in the internal stress value (or, decrease in effective stress) with strain/time appropriately described the observed decrease in creep rate during primary creep in the steel. The applicability of the model has been demonstrated by comparing experimental and predicted creep strain–time and creep rate–strain/time data of 9Cr–1Mo steel at 793 and 873 K for quenched and tempered and simulated post-weld heat treatment conditions. Irrespective of prior heat treatment and test temperature, the optimised parameters associated with the internal stress values exhibited linear variations with applied stress. The influence of prior heat treatment on primary and secondary creep characteristics of the steel is reflected on the rate constant values associated with the model. At all temperatures and heat treatment conditions, good agreement between the experimental and predicted steady-state creep rates demonstrate the further applicability of the model.